Temporal trends in healthcare utilization following primary melanoma diagnosis among Medicare beneficiaries. (9th July 2017) - Lott, J.P.; Wang, Q.; Titus, L.J.; Onega, T.; Nelson, H.D.; Weinstock, M.A.; Elmore, J.G.; Tosteson, A.N.A.
Summary: Background: Little is known about the impact of primary melanoma diagnosis on healthcare utilization and changes in utilization over time. Objectives: To evaluate population‐based temporal trends in healthcare utilization following primary melanoma diagnosis. Methods: We conducted a before‐and‐after multiple time series study of Medicare beneficiaries aged ≥ 66 years with primary melanoma diagnoses between 2000 and 2009 using the Surveillance, Epidemiology, and End Results Medicare database. Primary exposure was time from primary melanoma diagnosis at 3–6 months and 6–24 months postdiagnosis. Covariates included tumour‐, patient‐ and geographical‐level characteristics and healthcare utilization in the 6 months before diagnosis. Poisson regression was used to estimate population‐based risk‐adjusted utilization rates for skin biopsies, benign skin excisions, internal medicine office visits and dermatology office visits. Results: The study population included 56 254 patients with first diagnoses of primary melanoma. Most patients were ≥ 75 years old (56·8%), male (62·1%), and had in situ melanoma (42·4%) or localized invasive melanoma (45·9%). From 2000 to 2009, risk‐adjusted skin biopsy rates 24 months postdiagnosis increased from 358·3 to 541·3 per 1000 person‐years ( P < 0·001), and dermatology visits increased from 989·0 to 1535·6 per 1000 person‐years ( P < 0·001). Benign excisions and internal medicine visits remained stable. In 2000, risk‐adjusted skin biopsy rates 6 months postdiagnosis increased by 208·5 relative to the 6 months before diagnosis (148·7 vs. 357·2) compared with an observed absolute increase of 272·5 (290·9 vs. 563·1) in 2009. Trends in dermatology visits were similar. Conclusions: Utilization of skin biopsies and dermatology office visits following primary melanoma diagnosis has increased substantially over time. These results may inform optimization of care delivery for melanoma within the Medicare population. Abstract : What's already known about this topic? Primary melanoma diagnosis is associated with increased disease‐related economic costs; however, temporal trends in postdiagnosis healthcare utilization have not been evaluated. What does this study add? The results show that risk‐adjusted healthcare utilization following primary melanoma diagnosis increased precipitously from 2000 to 2009 across all stages and patient age groups. These results suggest that other nonclinical factors may be driving increased healthcare utilization and highlight opportunities for optimizing patterns of care delivery. Respond to this article Linked Comment:  Znaor. Br J Dermatol 2017;177 :625 Plain language summary available online